Implementasi Smart Tourism Situ Rawagede Bekasi sebagai Media Promosi dan Manajerial - Cep Adiwiharja; Ani Yoraeni; Zahra, Zahra; Nurul Aisyah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The partner for this Community Service Program (PKM) is Kelompok Pemuda Pecinta Lingkungan (KPPL) that manages the Situ Rawa Gede. Currently, promotional media is still manual, making this tourist attraction less known to visitors. The main issue faced by the partner is that the number of tourists visiting the park has not increased since the COVID-19 pandemic, necessitating an effective and efficient promotional medium to raise awareness the Situ Rawa Gede water park. Additionally, their administrative management and archiving are still in paper form, and their human resources lack knowledge and skills in information systems, particularly in using technology for tourism management. They also lack the necessary infrastructure to support the implementation of an information system. To address these issues, a web-based tourism information system will be developed using the Software Development Life Cycle (SDLC) method. This web-based system will provide broader benefits to users as can be accessed from anywhere with an internet connection, including descriptions, photos, locations, prices, and reviews from previous visitors. The methods used include observation, problem identification, problem formulation, and the implementation of activities as a solution, consisting several stages: preparation, assistance, and evaluation of the output.The target of this PKM activity is to realize the concept of smart tourism by increasing tourist visits and enhancing the partner's ability to run the tourism information system application. The outcome of this community service is an increase in KPPL's knowledge and skills, and the partner will have begun utilizing the information system for management and promotional media.